Pendekatan Dakwah Etis terhadap Kondisi Masyarakat Muslim Heterogen - Hajir Tajiri (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2008)
Da’wah has two faces the existence of which depends to da’i. When da’wah is done by da’i having minimum competency in knowledge and faith, the performance of da’wah become fearing, in-productive, horrify and fearsome. On the contrary if da’wah is done by da’i having a lot of knowledge, strong faith, competency in using relevant method, so da’wah’s performance become good and applicable to heterogeneous societies.